Revisiting ABC Transporters and Their Clinical Significance in Glioblastoma - Brandon Wee Siang Phon; Shalini Sundramurthi Chelliah; Dina El-Rabie Osman; Saatheeyavaane Bhuvanendran; Ammu Kutty Radhakrishnan; Muhamad Noor Alfarizal Kamarudin (Pharmaceuticals)
Background: The multiple drug-resistant phenomenon has long since plagued the effectiveness of various chemotherapies used in the treatment of patients with glioblastoma (GBM), which is still incurable to this day. ATP-binding cassette (ABC) transporters function as drug transporters and have been touted to be the main culprits in developing resistance to xenobiotic drugs in GBM. Methods: This review systematically analyzed the efficacy of ABC transporters against various anticancer drugs from 16 studies identified from five databases (PubMed, Medline, Embase, Scopus, and ScienceDirect). Results: Inhibition of ABC transporters, especially ABCB1, improved drug efficacies. Staple GBM phenotypes, such as GBM stem cells and increased activation of the PI3K/Akt/NF-κB pathway, have been implicated in the expression of several ABC transporters. Using the datasets in The Cancer Genome Atlas and Gene Expression Omnibus, we found upregulated ABC transporters that either negatively impacted survival in univariate analyses (ABCA1, ABCA13, ABCB9, ABCD4) or were independent negative prognosis factors for patients with GBM (ABCA13, ABCB9). Our multivariate analysis further demonstrated three ABC transporters, ABCA13 (Hazard Ratio (HR) = 1.31, p = 0.017), ABCB9 (HR = 1.26, p = 0.03), and ABCB5 (HR = 0.77, p = 0.016), with the administration of alkylating agents (HR = 0.41, p < 0.001), were independent negative prognosis factors for patients with GBM. Conclusions: These findings reinforce the important role played by ABC transporters, particularly by ABCA13, ABCB9, and ABCB1, which could be potential targets that warrant further evaluations for alternate strategies to augment the effects of existing alkylating agents and xenobiotic drugs.